Theory in Practice Increasing Professional Effectiveness - Argyris, Chris; Schön, Donald A. (San Francisco Jossey-Bass Publishers, 1974)
This book is a practical guide to the reform of professional education. It is also a beacon to theoretical thinking about human organizations, about their interdependence with the social structure of the professions, and about theory in practice.
Keywords: Professional education -- United States. Education. United States